A STYLISTIC STUDY OF LANGUAGE STYLE AND IMAGERY IN LEILA SALIKHA CHUDORI’S NOVEL PULANG: KAJIAN STILISTIKA GAYA BAHASA DAN CITRAAN DALAM NOVEL PULANG KARYA LEILA SALIKHA CHUDORI - Yusyama, Asep Yana; Aurelia, Aurelia (LLDIKTI Wilayah X, 2025)
Literary works are the result of artistic creation in the form of aesthetic language that contains elements of life expressed in oral or written form. One type of literary work is the novel. The novel that will be studied by the researcher is Pulang by Leila Salikha Chudori. The purpose of this study is to analyze the use of language style and imagery, including comparative language style, contrasting language style, connecting language style, and emphatic language style. There is also an analysis of six types of imagery, namely visual, auditory, kinesthetic, tactile, olfactory, and gustatory imagery. All are examined using stylistic analysis with descriptive qualitative research methods and purposive sampling techniques. The results of the study show that the use of language style in the novel Pulang is able to develop the emotions and imagination of the novel's readers. Not a few, the types of language styles displayed are able to carry the reader away by the atmosphere with the dominant use of comparison and contrast figures of speech. In addition, the imagery presented by Leila is able to describe a complex storyline with a series of words that evoke a narrative in the reader's mind regarding the atmosphere that the author wants to create. This is especially true of the dominant visual, auditory, and tactile descriptions. Based on this explanation, this study is expected to provide examples of the use of style and imagery that correlate with the meaning that the author wants to convey.